Peran Hukum Adat dalam Penyelesaian Sengketa Agraria di Indonesia: Kajian Empiris dengan Metode Komparatif - Pratiwi, Berliant; Soeparan, Poppy Fitrijanti; Wibisono, Widodo (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Agrarian disputes are a crucial issue in Indonesia, particularly in areas that serve as the centers of indigenous communities, where conflicts often arise between customary law and formal law. This study aims to analyze and compare customary and formal law's effectiveness in resolving agrarian disputes, focusing on indigenous regions with strong customary norms. The methodology employed includes semi-structured in-depth interviews and an analysis of customary legal documents, aimed at exploring respondents' perspectives and collecting data from relevant documents. The findings reveal that customary law often proves more responsive to the needs of local communities and creates fairer resolutions, whereas formal law tends to operate within a more universal framework and often overlooks local cultural values. The conclusion of this study underscores the importance of collaboration between customary law and formal law to enhance the effectiveness of agrarian dispute resolution and provides policy recommendations for the government to strengthen harmony between these two legal systems.